Inflation, Leverage, and Company Size and Their Effect on Profitability - Nugi Mohammad Nugraha; Annisa Arifianti Ramadhanti; Lia Amaliawiati (Pusat P2M Politeknik Negeri Batam, 2021)
The purpose of this study was to determine the effect of inflation, leverage, and company size on profitability in the plantation sub-sector companies listed on the Indonesia Stock Exchange for the period 2014-2018 either simultaneously or partially. This type of research is applied research with a quantitative approach. The research method used in this research is descriptive and verification methods. This study uses panel data regression analysis as a tool to process and analyze data because the data used is a combination of time series data and cross-section data. The data collection technique in this study uses library research and internet research. The data used in this study is a type of secondary data in the form of financial statements of plantation companies listed on the IDX from the 2014-2018 period. The population of this study was all plantation sub-sector companies listed on the Indonesia Stock Exchange, totaling 16 companies. The sample of this study was 14 companies obtained by purposive sampling. The results of this study indicate that simultaneously inflation, leverage, and firm size affect profitability. Partially leverage and company size do not affect profitability while leverage partially affects profitability. The value of the coefficient of determination (Adjusted R-squared) of 0.146134 or 14.61% indicates that variations in inflation, leverage, and company size have an effect of 14.61% on variations in profitability. While the remaining 0.853866 or 85.36% is influenced by variations in other variables not observed in this study.